Analisis Tujuan Pembangunan Berkelanjutan (SDGs): Mengurangi Kesenjangan di Provinsi Jawa Timur - Novilla Imriyani, Nindy (Jurnal Ilmu Ekonomi JIE, 2024)
One of the goals of sustainable development is to reduce income inequality. This research aims to find out what variables influence the income gap. The research objects were 38 regencies/cities in East Java. The data used in the study is secondary data for 2019 - 2022 sourced from the Central Statistics Agency (BPS) of East Java Province, which was taken using documentation techniques. The analytical tool used is panel data regression. The research results show that the average length of schooling positively and significantly affects income inequality. The Population Growth Rate has a negative and significant effect on Income Inequality. Economic Growth has a positive and significant impact on Income Inequality.